Treatment and Prevention Measures for Anoplocephalitis in Sheep and Goats - Achilov Shamsiddin Amanovich (Scientific Trends, 2024)
In this article, the effectiveness of anthelmintic drugs that have been and are being used in the treatment and prevention of anoplotcephalitis in sheep and goats is studied and analyzed. According to the analyzed literature, more than 200 different drugs have been tested in the treatment of monesiosis. Among the currently widely used drugs, high efficiency has been achieved using anthelmintic drugs such as albendazole, fenasal, fenbendazole, praziquantel, niclosamide, ricobendazole, clozalben, alvet suspension, moniesin, helmitcid, metsalbin, luxbendazole, levozan oral, nilzash s forte, monezol.
Keywords: Anoplotcephalatosis, monieziosis, tizaneziosis, avitelliniosis, anthelmintic, helminth, helminthosis.